Volatiles of Curcuma manggaVal. & Zijp (Zingiberaceae) from Malaysia - Ikarastika Rahayu Abdul Wahab; Polina D. Blagojevic; Niko S. Radulovic; Fabio Boylan (2011)
Analysis by GC and GC/MS of the essential oil obtained from Malaysian Curcuma manggaval. & zijp (Zingiberaceae) rhizomes allowed the identification of 97 constituents, comprising 89.5% of the total oil composition. The major compounds were identified as myrcene (1; 46.5%) and β-pinene (2; 14.6%). The chemical composition of this and additional 13 oils obtained from selected Curcuma L. taxa were compared using multivariate statistical analyses (agglomerative hierarchical cluster analysis and principal component analysis). The results of the statistical analyses of this particular data set pointed out that 1 could be potentially used as a valuable infrageneric chemotaxonomical marker for C. mangga. Moreover, it seems that C. mangga, C. xanthorrhizaroxb., and C. longa L. are, with respect to the volatile secondary metabolites, closely related. In addition, comparison of the essential oil profiles revealed a potential influence of the environmental (geographical) factors, alongside with the genetic ones, on the production of volatile secondary metabolites in Curcuma taxa.